The Constitutional Design of Weak Bicameralism: Re-evaluating the Legislative Powers of Indonesia's Regional Representative Council - A Rosyid Al Atok; Muhamad Sayuti Hassan; Sudirman Sudirman; Didik Sukriono (Faculty of Law Universitas Trunojoyo Madura, 2026)
The legislative function constitutes a fundamental pillar of parliament, operating in tandem with the oversight and budgetary functions. The establishment of the DPD within the Indonesian system was originally intended to construct a bicameral system that ensures checks and balances while accommodating regional interests. However, the current constitutional design reflects a flawed mechanism, culminating in a system of weak bicameralism that marginalizes the DPD's institutional role and renders it subordinate to the DPR. Although previous literature has extensively highlighted the DPD's limited authority, prior scholarship remains largely descriptive, focusing on normative reform proposals without adequately addressing the theoretical implications of this asymmetric power distribution. To bridge this research gap, this article employs a normative approach to re-evaluate the DPD's legislative authority, thereby advancing the existing discourse on constitutional design and institutional reform. The findings indicate that the existing anomaly in power distribution distorts the genuine mechanism of mutual control. As its principal theoretical contribution, this study reconceptualizes the parameters of effective asymmetric bicameralism by asserting that genuine territorial representation necessitates a substantive expansion of legislative powers, encompassing independent initiative rights, comprehensive deliberative participation, and decisive final views. This theoretical framework enriches comparative constitutional literature by demonstrating how reconfiguring asymmetric powers is essential to transforming constitutional anomalies into a balanced, effective, and accountable parliamentary system.